Anatomical accuracy of the KODEX‐EPD novel 3D mapping system of the left atrium during pulmonary vein isolation: A correlation with computer tomography imaging. (22nd February 2022) - Tovia Brodie, Oholi; Rav‐Acha, Moshe; Wolak, Arik; Ilan, Michael; Orenstein, David J.; Abuhatzera, Shalom; Glikson, Michael; Michowitz, Yoav
Abstract: Background: A novel 3D mapping system (KODEX‐EPD, EPD Solutions) enables catheter localization and real‐time 3D cardiac mapping. Objective: To evaluate left atrium (LA) anatomical mapping accuracy created by the KODEX‐EPD system during pulmonary vein isolation (PVI) compared with gold standard computed tomography (CT) images acquired from the same patients before the procedure. Methods: In 15 consecutive patients who underwent PVI, 3D mapping of the LA was created on the KODEX‐EPD system using the Achieve catheter. Pulmonary vein (PV), posterior wall, and appendage anatomy and diameters, were compared to the CT 3D reconstruction measured on the CARTO 3 system. Measurements were done independently by two physicians in each method. Linear correlation and agreement between CT and EPD measurements were assessed by Spearman correlation and Bland‐Altman plot. Results: Mean LA mapping time was 7.7 ± 3.6 min. Very high interobserver correlation was found for both EPD and CT measurements (Spearman r = .9). High correlation ( r = .75) was found between CT and EPD measurements. Bland‐Altman plot method revealed that measurements assessed by EPD were slightly higher than those assessed by CT. Mean difference was 3.5 mm, p  < .01. In 2 (13.5%) patients each, disagreement regarding the presence of a left common PV and a right middle accessory vein anatomy was seen. Conclusion: The new KODEX‐EPD mapping system allows quick and accurate mapping of the LA with high correlation to CT imaging. Some differences in left common and accessory right middle vein anatomy were seen. Abstract : Central illustration: An example of the anatomy created by the KODEX‐EPD system compared with the computed tomography (CT) image of the same patient. A standard 4 vein anatomy is demonstrated by both modalities, with early branching of the right inferior pulmonary vein. (A) KODEX‐EPD pre‐CRYO map during atrial fibrillation demonstrating connected pulmonary veins. (B) 3D CT image viewed on the CARTO auto‐segmentation module. (C, D) KODEX‐EPD posterior‐anterior and PANO images post‐CRYO map during sinus rhythm demonstrating pulmonary vein isolation with the same anatomy. (E)  Spearman correlation demonstrating a high correlation ( r = .75) between CT and KODEX‐EPD measurements, p  < .01.